2014
DOI: 10.1111/1365-2664.12225
|View full text |Cite
|
Sign up to set email alerts
|

Why model assumptions matter for natural resource management: interactions between model structure and life histories in fishery models

Abstract: Summary1. Bioeconomic models are increasingly used to provide benchmarks for harvest levels in wildlife and natural resource management, yet uncertainties related to model structure are underexplored. We investigate the importance of a range of uncertainties with a focus on model structure and life histories when estimating bioeconomic target reference point (TRPs) and assess the policy implications of ignoring these uncertainties. 2. We use three contrasting case studies to investigate the interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Previous studies have suggested that ignoring spatial structure can lead to overharvesting and localized depletion of sub-population components (e.g., Fu and Fanning 2004;Ying et al 2011;Hoshino et al 2014). Our findings further support the general concept that ignoring spatial structure and connectivity dynamics can lead to unintended consequences, and expands upon the types of spatial scenarios for which that applies.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Previous studies have suggested that ignoring spatial structure can lead to overharvesting and localized depletion of sub-population components (e.g., Fu and Fanning 2004;Ying et al 2011;Hoshino et al 2014). Our findings further support the general concept that ignoring spatial structure and connectivity dynamics can lead to unintended consequences, and expands upon the types of spatial scenarios for which that applies.…”
Section: Discussionsupporting
confidence: 86%
“…Accounting for only the biological aspects of spatial structure does not provide a complete overview of how spatial heterogeneity can impact estimation of biological reference points and related harvest strategies. The snapperlike results provide an indication of the increased complexities that result from spatial effort dynamics, which supports the findings of Hoshino et al (2014). A wide body of literature on Marine Protected Areas (MPAs) has demonstrated the importance of spatial harvest displacement for the determination of stock status indicators and achievement of conservation goals (e.g., Punt and Methot 2004;Pincin and Wilberg 2012;McGilliard et al 2015).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations